Development and Genetic Characterization of an Advanced Backcross-Nested Association Mapping (AB-NAM) Population of Wild × Cultivated Barley. Issue 3 (1st July 2016) - Nice, Liana M; Steffenson, Brian J; Brown-Guedira, Gina L; Akhunov, Eduard D; Liu, Chaochih; Kono, Thomas J Y; Morrell, Peter L; Blake, Thomas K; Horsley, Richard D; Smith, Kevin P; Muehlbauer, Gary J
Abstract: The ability to access alleles from unadapted germplasm collections is a long-standing problem for geneticists and breeders. Here we developed, characterized, and demonstrated the utility of a wild barley advanced backcross-nested association mapping (AB-NAM) population. We developed this population by backcrossing 25 wild barley accessions to the six-rowed malting barley cultivar Rasmusson. The 25 wild barley parents were selected from the 318 accession Wild Barley Diversity Collection (WBDC) to maximize allelic diversity. The resulting 796 BC2 F4:6 lines were genotyped with 384 SNP markers, and an additional 4022 SNPs and 263, 531 sequence variants were imputed onto the population using 9K iSelect SNP genotypes and exome capture sequence of the parents, respectively. On average, 96% of each wild parent was introgressed into the Rasmusson background, and the population exhibited low population structure. While linkage disequilibrium (LD) decay ( r 2 = 0.2) was lowest in the WBDC (0.36 cM), the AB-NAM (9.2 cM) exhibited more rapid LD decay than comparable advanced backcross (28.6 cM) and recombinant inbred line (32.3 cM) populations. Three qualitative traits: glossy spike, glossy sheath, and black hull color were mapped with high resolution to loci corresponding to known barley mutants for these traits. Additionally, a total of 10 QTL were identified for grain protein content. The combination of low LD, negligible population structure, and high diversity in an adapted background make the AB-NAM an important tool for high-resolution gene mapping and discovery of novel allelic variation using wild barley germplasm.